2014
DOI: 10.4081/mrm.2014.368
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume as an inflammation marker in active pulmonary tuberculosis

Abstract: Background: The mean platelet volume (MPV) reflects the size of platelets. It has been shown to be inversely correlated with level of the inflammation in some chronic inflammatory diseases. This prospective study aims to show the usability of MPV as an inflammation marker in patients with active pulmonary tuberculosis (PTB) by comparison with healthy controls. In addition, its relationships with other inflammatory markers such as C-reactive protein (CRP) and the erythrocyte sedimentation rate (ESR) as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
14
2
Order By: Relevance
“…Guclu et al showed that in patients with severe sepsis, PDW and MPV levels were higher than non-severe sepsis (8). On the other hand, Gunluoglu et al found lower MPV levels in active pulmonary tuberculosis cases but this did not reflect the severity of disease (9).…”
Section: █ Discussionmentioning
confidence: 98%
“…Guclu et al showed that in patients with severe sepsis, PDW and MPV levels were higher than non-severe sepsis (8). On the other hand, Gunluoglu et al found lower MPV levels in active pulmonary tuberculosis cases but this did not reflect the severity of disease (9).…”
Section: █ Discussionmentioning
confidence: 98%
“…We also found that a decreased MPV value may be associated with the highest risk of diagnosing VTE in patients with active cancer, thus sup-porting the data recently published by Riedl et al 6 Interestingly, a similar inverse association has also been observed in patients with brain injury after mild head trauma, wherein the frequency of decreased MPV values was 10-and 17-fold higher in patients with negative and positive computed tomography (CT) scans, respectively. 11 Further clinical investigations also showed that reduced platelet size can be observed in patients with chronic obstructive pulmonary disease, 12 pulmonary tuberculosis, 13 and necrotizing pancreatitis. 14 Interestingly, Mutlu et al retrospectively studied 43 patients with cancer who developed VTE and observed that MPV values at the time of development of venous thrombosis were significantly lower compared with the values recorded at the time of cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in accordance with our ndings, in that there were no signi cant differences between TB patients and healthy controls. Gunluoglu et al suggested that the value of MPV was slightly decreased in TB patients, and the MPV never re ected the severity of tuberculosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of MPV in TB is disputed. A study conducted by Gunluoglu et al suggested that MPV, as an in ammation marker, decreased in active pulmonary tuberculosis related to the formation of microthrombi in TB cavities [24].…”
Section: Introductionmentioning
confidence: 99%